β3-Adrenoceptors as Putative Regulator of Immune Tolerance in Cancer and Pregnancy - Calvani, Maura; Dabraio, Annalisa; Subbiani, Angela; Buonvicino, Daniela; De Gregorio, Veronica; Ciullini Mannurita, Sara; Pini, Alessandro; Nardini, Patrizia; Favre, Claudio; Filippi, Luca (Frontiers in Immunology, 2020)
Understanding the mechanisms of immune tolerance is currently one of the most important challenges of scientific research. Pregnancy affects the immune system balance leading the host to tolerate embryo alloantigens. Previous reports demonstrated that β-adrenergic receptor (β-ARs) signaling promotes immune-tolerance by modulation of NK and Treg, mainly through the activation of β2-ARs, but recently we have demonstrated that also β3-ARs induce an immune-tolerant phenotype in mice bearing melanoma. In this report, we demonstrate that β3-ARs support host immune tolerance in maternal microenvironment by modulating the same immune cells populations as recently demonstrated in cancer. Considering that β3-AR are modulated by oxygen levels, we hypothesize that hypoxia, through the upregulation of β3-AR, promotes the biological shift towards a tolerant immunophenotype, and that this is the same trick that embryo and cancer use to create an aura of immune-tolerance in a competent immune environment. This study confirms the analogies between fetal development and tumor progression and suggests that the expression of β3-ARs represents one of the strategies to induce fetal and tumor immune tolerance. This study confirms the analogies between fetal development and tumor progression and suggests that the expression of β3-ARs represents one of the strategies to induce fetal and tumor immune tolerance.